USING TAGUCHI METHOD IN DEFINING CRITICAL ROTOR POLE DATA OF LSPMSM CONSIDERING THE POWER FACTOR AND EFFICIENCY - (:unkn) unknown (UNIV OSIJEK, TECH FAC, 2017)
This paper presents determining of critical rotor pole data of line-start permanent magnet synchronous motor (LSPMSM). The critical rotor pole data of LSPMSM considering the power factor and efficiency are investigated by using Taguchi's method. This determining process is carried out to prevent waste of time while 3D analysis is made. Two-dimensional (2D) dynamic finite element analysis (FEA) models are deployed to evaluate the performances of LSPMSM. To avoid the task of creating the geometry of the motor in Maxwell 3D, RMxprt has initially been used here to provide a convenient way of expediting. This study has performed 2 different ways for optimization. They were optimization using Taguchi's method and without using Taguchi's method. The method without using Taguchi method is known as a conventional method. The experimental comparisons between these ways have demonstrated that remarkable decrease in time-loss in the power factor and efficiency can be obtained by the proposed method.
Keywords: design of experiment; finite element analysis; line-start permanent magnet motor; optimization; power factor and efficiency; Taguchi; MOTOR; DESIGN